A rain energy harvester using a self-release tank. (15th January 2021) - Bao, Bin; Wang, Quan
Graphical abstract: Highlights: A novel rain energy harvester using a self-release tank is proposed. The self-release tank automatically releases the rainwater. The maximum peak-peak piezo-voltage in one working period can achieve 160 V. The proposed and traditional energy harvesters can be used in a complementary way. Abstract: This research proposes a novel rain energy harvester to scavenge the potential energy of rainfall. The proposed structure is composed of three parts: a funnel structure with large contact surface for collecting rainwater; a self-flip square container considered as a self-release tank; and a piezoelectric cantilever beam with a baffle plate for energy conversion. Traditionally, the rain energy harvester techniques rely on direct raindrop impact induced kinetic-to-electric energy transfer via piezoelectric materials. Different from the traditional methods, the rainwater is firstly collected in the self-release tank by using the funnel structure in the proposed method. And then when the rainwater is full of the tank, the tank will release the rainwater by itself without external sensor monitoring and active control. The released rainwater is applied to actuate the baffle plate of the piezoelectric cantilever beam for harvesting the potential rainwater energy. Working principle of the proposed structure and the self-release function of the tank are investigated theoretically and experimentally in detail. Results show that for the proposed energy harvester in the open circuit condition under a low height H  = 24 cm, the maximum output peak-peak piezoelectric voltage in one working period can achieve 160 V. The 100 μF capacitor can be quickly charged to the saturation voltage 3.3 V using the energy harvesting circuit LTC3588 after 4 working periods.